ANALISIS KEMAMPUAN BERFIKIR REFLEKTIF MATEMATIKA DENGAN GAYA BELAJAR VISUAL, AUDIOTORIAL DAN KINESTETIK SISWA KELAS VIIIA SMP NEGERI 2 LINGGABAYU - Nurdalilah Nurdalilah (JURNAL MathEdu (Mathematic Education Journal), 2021)
Reflective thinking is the higher order thinking skills. One effort to optimize this ability is to know the learning style of students. To know it then conducted a research with descriptive qualitative type with the aim to know the students' reflective thinking ability with visual, auditorial, and kinesthetic learning styles. The subject of this research is class VIII A in SMPN 2 Linggabayu which is chosen by purposive Sampling on geometry problem. The results of data analysis show, visual, auditorial and kinesthetic students have not been able to identify the formula or concept used because it does not provide the overall answer. Visual students and kinesthetic students are able to evaluate correctly, clearly, less systematically, but are complete while the auditorial students are able to evaluate them correctly, clearly, systematically, and completely. Visual students and auditorial students give incomplete answers and wrong answers and do not give an analogy while kinesthetic students give complete answers but wrong answers and do not give an analogy. Visual students give incomplete calculations, wrong answers and do not give generalizations with reasons, auditorial students provide correct calculations, the final answer is correct but does not provide generalization with the reasons while kinesthetic students provide correct calculation, the final answer is correct and give generalization with the reasons. The visual student explains in his own subject and the correct answer, the auditorial student explains by explaining it at length and right answers while the kinesthetic student explains with the correct answer. Visual students are able to provide interpretation but not yet complete and correct calculation, the auditorial student has not been able to provide interpretation but the calculation is correct, while the kinesthetic students are able to provide good interpretation with the correct calculation.